ECONOMIC PRESSURE, PARENT-ADOLESCENT INTERACTION, AND EARLY MARRIAGE MOTIVATION - Cindy Arbelia; Yulina Eva Riany (Journal of Child, Family, and Consumer Studies, 2022)
The marriage that occurs at a child's age has a negative impact on the development of children and their families. Child marriage is not only caused by external factors but also by internal factors, such as the desire of teenagers can encourage child marriage. This study aimed to determine the effect of economic pressure and parent-adolescent interactions on adolescent motivation to marry early. This study uses a cross-sectional study design with analysis using Microsoft Excel and SPSS 25 for Windows. The number of research samples, as many as 165 adolescents in Jabodetabek obtained by voluntary sampling by distributing online questionnaires. The research instrument consisted of an objective economic pressure instrument, a subjective economic pressure instrument, a parent acceptance-rejection questionnaire instrument, and an early marriage instrument. The correlation analysis showed that subjective economic pressure positively correlates with early marriage motivation. A mother's education has a significant negative correlation with early marriage motivation. The regression analysis showed that subjective economic and parent-adolescent interaction on the dimensions of violence and psychological control significantly positively affects early marriage motivation. Parents are expected to increase positive interactions by reducing violence and psychological control on children to reduce the motivation for early marriage.